Da tropodifusão à fibra óptica: os desafios geográficos para a formação do território tecnológico do Amapá, Brasil - Marco Antônio Leal da Silva; José Francisco de Carvalho Ferreira (Confins)
This text presents the configuration of the technological territory of Amapá (Brazil), based on the historical context of the dispersion of telecommunications networks in the Brazilian space and the verification of the geographical challenges and their implications for the technological development of the territory in the extreme north of Brazil. Methodologically, it is a set of images commented on for their relevance on the subject, since the discussion on technological territory is in its beginning, with few studies about the formation of technological networks in Amapá that connected the region to the global network. The results indicate that the formation of technological networks in Amapá is linked to political initiatives of the national government and, also, to the efforts of local actors, who started a process of modernization, due to the historical precariousness experienced by this peripheral region.